Ultrasound guided spinal catheter insertion in piglet: preliminary results. (November 2017) - Romagnoli, Noemi; Lambertini, Carlotta; Ventrella, Domenico; Floriano, Dario; Elmi, Alberto; Barone, Francesca; Bacci, Maria L.
Abstract: Objective: To describe the ultrasound (US) evaluation of the cervical, thoracic and lumbar spinal tracts in piglets and to evaluate the feasibility of the ultrasound guided spinal catheter placement in newborn and paediatric piglets. Study design: Prospective experimental study. Animals: A total of two piglet cadavers (age, 7 and 14 days) and eight commercial crossbreed piglets divided into four groups according to age: 7 (P7), 14 (P14), 21 (P21) and 28 (P28) days. Methods: In the first part of the study an ultrasound examination of the spinal tract was performed in piglet cadavers applying the transverse and the longitudinal approaches in sternal and lateral recumbencies. In the second phase, the piglets were anaesthetized with sevoflurane. A US examination with a 10 MHz linear probe was performed and a spinal catheter was introduced between the spinous processes of L2 and L3 lumbar vertebrae using an in-plane technique and its advancement was monitored with the probe. At the end of procedure, the catheter was removed. The piglets recovered from anaesthesia and were monitored for one week. Results: In phase I the authors identified the paramedian longitudinal approach as the most feasible for spinal structure evaluation in piglets. In phase II, the paramedian longitudinal views enabled a good visualization of the spinal cord and of the catheter advancement up to the cisterna magna in groups P7 and P14. In groups P21 and P28 it was not possible to visualize the neuroaxial structures and the spinal catheter using the same approach. No clinical alterations were recorded during the procedure or the following days. Conclusions and clinical relevance: US-guided spinal catheter placement appeared a feasible technique in piglets younger than 14 days but it is not useful in older piglets.